Asian Yearbook of International Law, Volume 29 (2023) - Lee, Hee Eun,; Lee, Seokwoo, (Asian Yearbook of International Law ;, 2025)
Launched in 1991, the Asian Yearbook of International Law is a major internationally-refereed yearbook dedicated to international legal issues as seen primarily from an Asian perspective. It is published under the auspices of the Foundation for the Development of International Law in Asia (DILA) in collaboration with DILA-Korea, the Secretariat of DILA, in South Korea. When it was launched, the Yearbook was the first publication of its kind, edited by a team of leading international law scholars from across Asia. It provides a forum for the publication of articles in the field of international law and other Asian international legal topics. The objectives of the Yearbook are two-fold: First, to promote research, study and writing in the field of international law in Asia; and second, to provide an intellectual platform for the discussion and dissemination of Asian views and practices on contemporary international legal issues. Each volume of the Yearbook contains articles and shorter notes; a section on Asian state practice; an overview of the Asian states' participation in multilateral treaties and succinct analysis of recent international legal developments in Asia; a bibliography that provides information on books, articles, notes, and other materials dealing with international law in Asia; as well as book reviews. This publication is important for anyone working on international law and international relations.